Isolation of root endophytic bacteria from tomato and its biocontrol activity againts fungal diseases - ABDUL MUNIF; JOHANNES HALLMANN; RICHARD A SIKORA (Microbiology Indonesia, 2012)
Endophytic bacteria have gained attention due to their interesting features related to plant growth and health stimulation. The objective of this research was to determine the populations and spectrum of indigenous root endophytic bacteria from tomato (Lycopersicon esculentum) and the biocontrol activity of the bacteria for plant protection. The isolation procedure of these endophytic bacteria was done using surface-sterilization method using alcohol and sodium hypochlorite (NaOCl). General medium trypsic soy agar (TSA) was used as the growth medium for isolation. The total population density of endophytic bacteria recovered from tomato roots ranged from 1.0 to 4.4 (in log10Â  scale) CFU g-1 fresh root weight. A total of 564 strains of endophytic bacteria were isolated from tomato plants grown in West Java, Indonesia. Endophytic bacterial strains were identified based on their fatty acid profile using FAME-GC-MIDI system. Fifty species and 32 genera of endophytic bacteria were found in association with tomato root. The most abundant endophytic bacterial genera were Bacillus spp. and Pseudomonas spp. One hundred and eighty oneÂ  bacterial strains were tested for their in vitro antagonism towards Rhizoctonia solani, Fusarium oxysporum f.sp. radicis-lycopersici, and F. oxysporum f.sp. lycopersici. Fourteen strains showed antagonism against R. solani, nine strains against F. oxysporum f.sp. radicis-lycopersici and seven strains against F. oxysporum f. sp. lycopersici. The close relationship between endophytic bacteria and their hosts make them ideal candidates for biological control and plant growth promotion.